Proceedings of the ACM International Conference on Image and Video Retrieval 2009
DOI: 10.1145/1646396.1646441
|View full text |Cite
|
Sign up to set email alerts
|

Spatial extensions to bag of visual words

Abstract: The Bag of Visual Words (BoV) paradigm has successfully been applied to image content analysis tasks such as image classification and object detection. The basic BoV approach overlooks spatial descriptor distribution within images. Here we describe spatial extensions to BoV and experimentally compare them in the VOC2007 benchmark image category detection task. In particular, we compare two ways for tiling images geometrically: soft tiling approach-proposed hereand the traditional hard tiling technique. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…For example, Viitaniemi et al observed that manually designed tilings achieve reasonable improvement over the SPM on the Pascal VOC dataset [24]. Similar observations have been confirmed on other datasets.…”
Section: Related Workmentioning
confidence: 57%
See 2 more Smart Citations
“…For example, Viitaniemi et al observed that manually designed tilings achieve reasonable improvement over the SPM on the Pascal VOC dataset [24]. Similar observations have been confirmed on other datasets.…”
Section: Related Workmentioning
confidence: 57%
“…However, the problem is still tractable given the reasonable masks including the commonly used masks in the literature [12,24,30,21]. The numbers of all possible set partitions, tilings and equal tilings on different masks are listed in Table 1, where the Parameter column lists the parameters used in generating the masks 1 , e.g.…”
Section: Tiling Function Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…The final spatial pyramid kernel is implemented as concatenating weighted histograms of all features at all sub-regions. The traditional bag-of-visual words scheme discards any spatial information; hence many methods utilizing this concept also introduce different spatial extensions [7,24].…”
Section: Related Workmentioning
confidence: 99%
“…In (Sharma and Jurie, 2011), Sharma et al propose to learn the best discriminative grid splitting optimizing a given classification task. In (Viitaniemi and Laaksonen, 2009), Viitaniemi et al compare techniques of soft tiling and hard tiling. Furthermore, some works propose to learn or adapt weights rather than using fixed ones, as in (Harada et al, 2011).…”
Section: Introductionmentioning
confidence: 99%